2019
DOI: 10.1093/jamia/ocz140
|View full text |Cite
|
Sign up to set email alerts
|

Detecting conversation topics in primary care office visits from transcripts of patient-provider interactions

Abstract: Objective Amid electronic health records, laboratory tests, and other technology, office-based patient and provider communication is still the heart of primary medical care. Patients typically present multiple complaints, requiring physicians to decide how to balance competing demands. How this time is allocated has implications for patient satisfaction, payments, and quality of care. We investigate the effectiveness of machine learning methods for automated annotation of medical topics in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…PĂ©rez-Rosas et al, 2019 showed that as they increased the amount of data in their training set they observed significant improvement in prediction accuracy. Aligned with this finding, frequently observed codes (i.e., categories) in a dataset Howes et al, 2013;Perez-Rosas et al, 2017;Perez-Rosas et al, 2019;Xiao et al, 2015;Park et al, 2019;Flemotomos et al, 2018. Random Forest 7 Carcone et al, 2019Imel et al, 2015;Mieskes and Stiegelmayr, 2018;Blanchard et al, 2016a;Blanchard et al, 2016b;Donnelly et al, 2017;Wang et al, 2014.…”
Section: Article In Pressmentioning
confidence: 77%
See 2 more Smart Citations
“…PĂ©rez-Rosas et al, 2019 showed that as they increased the amount of data in their training set they observed significant improvement in prediction accuracy. Aligned with this finding, frequently observed codes (i.e., categories) in a dataset Howes et al, 2013;Perez-Rosas et al, 2017;Perez-Rosas et al, 2019;Xiao et al, 2015;Park et al, 2019;Flemotomos et al, 2018. Random Forest 7 Carcone et al, 2019Imel et al, 2015;Mieskes and Stiegelmayr, 2018;Blanchard et al, 2016a;Blanchard et al, 2016b;Donnelly et al, 2017;Wang et al, 2014.…”
Section: Article In Pressmentioning
confidence: 77%
“…In this context, the machine learning methods were designed to automatically assign codes from the behavioural coding measures to overt interactions recorded in the dataset (e.g., words/utteran- (Atkins et al, 2014;Can et al, 2015;Can et al, 2012;Can et al, 2016;Cao et al, 2020;Carcone et al, 2019, Study 1;Chakravarthula et al, 2015;Chen et al, 2019;Gibson et al, 2017;Gibson et al, 2016;Gupta et al, 2014;Hasan et al, 2019;Hasan et al, 2018;Imel et al, 2015;Perez-Rosas et al, 2017;Perez-Rosas et al, 2019;Singla et al, 2018;Tanana et al, 2016;Xiao et al, 2012;Xiao et al, 2015;Xiao, Can, et al, 2016;Xiao, Huang, et al, 2016) Medical care, provider-patient clinical interactions (Carcone et al, 2019, Study 2;Park et al, 2019) Education (teachers) (Blanchard et al, 2016a;Blanchard et al, 2016b;Donelly et al, 2017;Donnely et al, 2016a;Donnelly et al, 2016b;Samei et al, 2014;Samei et al, 2015;Song et al, 2020;Suresh et al, 2019;Wang et al, 2014) Counselling, (counsellors), (Althoff et al, 2016;Flemotomos et al, 2018;Gallo et al, 2015;Gaut et al, 2017;Goldberg et al, 2020…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One solution is to identify the category of each speaker turn (utterance), allowing for topic blocks to be identified in the transcripts (topic segmentation). 22,26 Targeted information extraction and summarization can then be applied to the identified topics. 7,22 The topics can be based on predetermined categories 22 or the components of a traditional medical encounter (chief complaint, family history, social history).…”
Section: Challenge 1: Audio Recording and Speech Recognitionmentioning
confidence: 99%
“…HMM was used in detecting topics from transcripts of patient-provider conversations. 103 This could improve patient satisfaction, cost-effectiveness, and care. Infinite HMMs can be used as a powerful tool to analyze single molecule sequential data without any prior setting of stat, which is required infinite HMMs.…”
Section: Tools For Time Domain Analysismentioning
confidence: 99%